STUDI LITERATUR TENTANG STRATEGI PENGELOLAAN EVENT OLAHRAGA YANG EFEKTIF DAN EFISIEN - Heri Auliaji; Sutan Rionaldo Hutabarat; Tasya Amanda Pohan; Pyriel Sinaga; M.Arif Prastiyo; Franz Mixhael Keliat; Tengku Raja D.Z Manurung; Muhammad Ridho Syuhada; Hery Kresfo Hutabarat; Irfan Hanafi; Siti Rahima Gultom; Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sporting events play a crucial role in increasing community participation, athlete achievement, and the economic and social impacts of a region. The success of sporting events depends heavily on effective and efficient management strategies. This study aims to examine various sporting event management strategies based on literature reviews from various journals and scientific sources. The method used is a literature review, analyzing various studies related to sporting event management. The study results indicate that the success of sporting events is influenced by thorough planning, coordination between stakeholders, optimal resource management, utilization of digital technology, risk management, and post-event evaluation. These strategies can improve the quality of the event, participant satisfaction, and the efficiency of budget and resource use. Therefore, implementing an integrated management strategy is a key factor in creating sustainable and competitive sporting events.